Diversifying Dietary Options: A Strategic Path to Reducing Stunting in East Nusa Tenggara (NTT) - Karim, Mohammad Monjurul; Arisonaningtyas, Dina; A. Kikon, Rhondemo (Knowledge Dynamics, 2025)
Stunting remains a pressing public health issue in Indonesia, with East Nusa Tenggara (NTT) recording a prevalence of 37% in 2024- nearly twice the national average. The challenge lies less in calorie deficiency and more in poor diet quality driven by limited dietary diversity. While Indonesia has reduced its national stunting rate to 19.8%, progress in high-burden provinces like NTT remains slow, hindered by inadequate resource allocation and continued reliance on water-intensive rice cultivation in a predominantly dry climate. Locally resilient crops such as sorghum (Sorghum bicolor) and moringa (Moringa oleifera) present viable solutions. Both crops thrive in semi-arid conditions and offer nutrient-dense alternatives to rice, addressing protein, iron, and vitamin A deficiencies that contribute to stunting. Recent studies in NTT show that sorghum- and moringa-based foods improve child growth indicators, demonstrating their potential as scalable interventions. Promoting diversified, locally rooted food systems can not only combat stunting but also reduce wasting and underweight, making food diversification a cornerstone of sustainable nutrition strategies in NTT.